S'Orienter : l'orientation en groupe comme espace de développement de la capacité à réaliser des choix éducatifs et professionnels - Patricia Dionne; Frédéric Saussez; Amélie Simard (Nantes Université, 2022)
In Quebec, the new Policy on Educational Success is reflected, among other things, in a dispositive whitch based success on the establishment of graduation targets to be achieved by educational institutions. To counter the negative influence of not having a diploma, policy initiatives seek to better target interventions directed at young adults to support their educational and vocational guidance. The S'Orienter Program was designed to debate stereotypical representations of young adults in order to support the development of their power to act and their consciousness regarding their educational and professional choices. Our analysis presents the influence of this group career counseling on the ability of young adults to project themselves into the future and to make educational and professional choices. We conceptualize the emancipatory function of intervention from the analysis of the consciousness - through the appropriation of conceptual instruments - of the emotions and norms that influence these choices.